A legal analysis of legal protection for female victims of sexual violence is reviewed based on Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (TPKS Law) - Ragiel Nur Marvo; Padrisan Jamba (Jurnal Multidisiplin Sahombu, 2026)
Sexual violence against women has become an increasingly serious social issue in Indonesia, with data showing a significant increase in reported cases, often linked to gender inequality and inadequate legal protection. Prior to the enactment of Law Number 12 of 2022 concerning Crimes of Sexual Violence (TPKS Law), the legal framework for protecting victims had weaknesses, such as limited coverage, a focus primarily on criminal aspects without a holistic approach to victims' rights, and a lack of effective mechanisms for recovery and restitution. This study aims to analyze the form and effectiveness of legal protection for women victims of sexual violence under the TPKS Law. The research method used is normative juridical, with a legal and conceptual approach, through analysis of legal texts, court decisions, and related legal concepts. Key findings indicate that the TPKS Law expands protection for victims through medical and psychological rights, protection from revictimization, social recovery, and more comprehensive restitution. In conclusion, the TPKS Law is a progressive legal instrument for protecting victims of sexual violence. However, its implementation still faces challenges such as limited resources, public awareness, and harmonization with other regulations.